PELAKSANAAN BAURAN PROMOSI PAKET WISATA PADA PT. ARAS HIJRAH TOUR & TRAVEL PEKANBARU - Sri Rahmah Novita; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to find how the implementation mix promotion package at PT. Aras Hijrah Tour & Travel Pekanbaru. The research method that is used is qualitative descriptive. The main informants of the study were Director PT.Aras Hijrah Tour & Travel Pekanbaru, supporting informants were Manager and ticket section. Data collection is done by direct interview and documentation. Data analysis is done through the stages of data collection, data reduction, data presentation and conclusion. The results of this study concluded that has been PT. Aras Hijrah Tour & Travel uses 4 (four) promotional mix elements in the sale of its tour packages,that is : 1) Advertising, (2) Sales Promotion, (3) Public Relations, (4) Direct marketing. Implementation the promotional mix of PT. Aras Hijrah Tour & Travel it’s good, this can be seen from the combination of the promotional mix, especially for advertising and public relations. Keywords: Promotion Mix , Tour Package, PT. Aras Hijrah Tour & Travel